An Ecofeminist Reading of Fleur and Lulu in Louise Erdrich’s Novel Tracks - Markasović, Valentina (Anafora, 2024)
Tracks by Louise Erdrich is a novel dealing with the struggles of Native Americans at the beginning of the twentieth century, but within that broader frame—it also speaks out about the connection between the colonial oppression of nature and the subjugation of women. Although some ecocritical and ecofeminist readings of the novel, especially relating to Fleur Pillager, are available, not much has been written on the character of Lulu Nanapush as presented in Tracks. Therefore, this article analyses Fleur Pillager and Lulu Nanapush to discover how the tenets of ecofeminism are implemented in the novel. The research relies on the theories of different ecofeminist and postcolonial authors. After establishing the colonial background of conjoined oppression of women and nature, the article focuses on how Fleur embodies and protects nature, while Lulu begins to lose her connection to nature due to her colonial background. Thus, strategic essentialism of the kind could be understood as having been implemented with the aim of underlining the exploitation of Native American women by settler colonizers, as well as the eradication of nature.